Fundamental of Entrepreneurship ENT300 : House Of Donut / Rozalina Bin Suhai ... [ et al. ] - Suhai, Rozalina; Mohd Norizam, Nur Asyikin; Khairul Adha, Muhammad Imran; Abdul Khalid, Mohamad Zulfadlie; Hamzah, Mohd Azmeer (2016)
The business plan of House of Donut is proposed so that it can be taken by comprehensive manner. Business Plan sets out how the owners andmanagers of a business intend to realize its objective. Besides, enables management to structured way and to set out the stages in * the achievement of the business objectives. This business plan also gives the business the opportunity to assess on business in ftmtry in the future. All parhrer of House of Donut have decided to form parhrership business which we carl spend our interest in our own daugh nuts and beverages industry. The business is in form of enterprise which consist four shareholders. House of Donut serves various tlpe of flavour which is very tasty and smooth.